Peran Aparatur Pemerintah Desa dalam Meningkatkan Partisipasi Politik Penyelenggaraan Pemilu Tahun 2019 Desa Mlagen, Magelang - Bhakti, Indira Swasti Gama; Gunawan, Tri Agus (Universitas Negeri Surabaya, 2020)
Election (Election) is one of the means of democracy in the implementation of popular sovereignty within the Unitary Republic of Indonesia which is based on the Pancasila and the 1945 Constitution. Through elections conducted the people can elect leaders who are expected to be able to bring change towards a better life. Elections are also a means for the people to choose their trusted representatives to carry out various government affairs. Elections must be based on people's awareness to vote, not because of coercion or pressure. The higher the level of people's participation in the election, it means that the higher the level of their political awareness. Villagers who on average are still well educated understand politics only limited to a party of the people which is carried out every five years, and not a few political participation by the community is still influenced by movements from the ruling parties including the village head. The role of the village head is very important to be needed with the situation of rural educated people who are still quite low and most are farmers, this is what was described in Mlagen Village, Bandongan District. The role of the village head is very necessary in order to increase public political participation in the presidential election in 2019. The research method used is a qualitative research method with descriptive analysis techniques. Data collection is done through observation, interviews and documentation. Research data sources are key informants, informants, research sites and documents.